AKIBAT HUKUM TERHADAP PELANGGARAN SURAT IJIN USAHA PERDAGANGAN DI KABUPATEN GIANYAR - A.A. Mas Adi Trinaya Dewi (Fakultas Hukum Universitas Dwijendra, 2021)
The increasing interest of the private sector to do business in company activities, except in fields that control the lives of many people and are strategic. The role of the government is to regulate what is included in government programs, especially the provision of facilities and infrastructure. One of them is in the form of regulations in the form of granting trading business licenses. The problems that arise include: What are the legal consequences of a mini market trading business if it does not have a Trading Business License (SIUP) and what are the actions taken by the authorized official against violators of the Mini Market Trading Business License (SIUP). The approach to the problem used in this research is normative juridical. On the basis of the discussion in the analysis described above, the following conclusions can be drawn: The legal consequences of a mini market business if it does not have a trading business license (SIUP) include administrative sanctions such as summons to be directed to seek SIUP, written warnings, temporary suspension of SIUP. and finally the revocation of SIUP in accordance with Gianyar Regency Regulation Number 6 of 2005 concerning Trading Business Permits (SIUP), while the criminal sanction is imprisonment for a maximum of 3 (three) months or a maximum fine of 4 (four) times the amount of retribution owed. Actions taken by authorized officials against violations of trade business permits (SIUP) include forming an integrated team involving stikeolders such as Satpol PP, Police, the legal department, the economic division and the regional supervisory agency (Bawasda), to oversee all business activities such as mini markets, supermarkets and hypermarkets in order to seek business licenses as a means of legality in carrying out their business activities.